MODERN TECHNOLOGIES FOR THE PRESERVATION AND DEVELOPMENT OF LANGUAGES AND CULTURES OF INDIGENOUS PEOPLES OF THE REPUBLIC OF SAKHA (YAKUTIA) - Polikarpova, Evdokia; Marfusalova, Venera; Nikitina, Nurguyana; Atlasova, Elida; Krivoshapkina, Ekaterina (Revista Inclusiones, 2020)
The issues addressed in the article are of particular relevance due to the negative dynamics in functioning of the native languages of indigenous peoples of the Sakha Republic (Yakutia). The picture emerging from observations in the places of compact residence of indigenous peoples (Sakha, Even, Evenki, Yukagir and Dolgan) is characterised by neglecting native languages and using the Russian language instead. Today it is officially recognized that the active carriers of native languages and cultures can be found only among people of older generations. Therefore, preservation and development of native languages and culture of indigenous peoples of the Sakha Republic is really a very urgent issue. The development of methodology for the revitalization of languages and culture can greatly contribute to solving the pressing problems of the current socio-cultural situation.